2023
DOI: 10.3390/antiox12071480
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin as a Potent Antioxidant for Promoting Bone Health: An Up-to-Date Review

Iswari Davan,
Sharida Fakurazi,
Ekram Alias
et al.

Abstract: In recent years, bone loss and its associated diseases have become a significant public health concern due to increased disability, morbidity, and mortality. Oxidative stress and bone loss are correlated, where oxidative stress suppresses osteoblast activity, resulting in compromised homeostasis between bone formation and resorption. This event causes upregulation of bone remodeling turnover rate with an increased risk of fractures and bone loss. Therefore, supplementation of antioxidants can be proposed to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 178 publications
0
2
0
Order By: Relevance
“…A multitude of studies highlights the core position occupied by oxidative stress in the senescence process and the pathophysiology of OP. Antioxidants serve a vital protective function by countering ROS, preserving cellular redox equilibrium, and thereby effectively shielding cells from oxidative injury caused by ROS, thereby offering the potential for suppressing the development of OP (Damani et al, 2022;Davan et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multitude of studies highlights the core position occupied by oxidative stress in the senescence process and the pathophysiology of OP. Antioxidants serve a vital protective function by countering ROS, preserving cellular redox equilibrium, and thereby effectively shielding cells from oxidative injury caused by ROS, thereby offering the potential for suppressing the development of OP (Damani et al, 2022;Davan et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that supplementing with antioxidants is a key approach to reducing the impact of free radicals, preventing oxidative damage, and countering the negative effects of oxidative stress on bone health (Damani et al, 2022;Davan et al, 2023). Figure 1 illustrates the oxidative stress and antioxidant mechanisms involved in the development of OP.…”
Section: Introductionmentioning
confidence: 99%
“…Potential auxiliary therapeutic agent alone or in combination in treating prostate cancer [31] Helped with skin cancer by reducing the dryness caused by UV and increased MED [34] 2.2 Anti-diabetic activity Lowered blood pressure and improves glucose metabolism in type 2 diabetic patients [35] Significantly reduced the pain caused by diabetic neuropathy [36] 2.3 Anti-inflammation activity Enhanced the immune response [2] 2.4 CVD prevention Improved cardiac contractility and exercise tolerance [37] 2.5 Neuroprotective activity Improved cognitive performance and brain health [27,38] 2.6 Sports performance enhancer Promoted mental and physical fatigue [40] Improved the temporary reduction of human antioxidant capacity [41] Improved exercise performance and enhanced fat oxidation [42] Increased walking endurance and reduced oxidative stress [44] 2.7 Skin aging prevention Reduced skin dryness and increased skin moisture [1] Enhanced facial skin rejuvenation [49] Improved skin elasticity [1,50] 2.8 Eye health promotor Improved central retina function [4] Reduced total hyperoxides [51] 2.9 Other health benefits Improved oocyte maturation and rates of high-quality embryos [52] Effective in cryopreservation of human sperm [53] Decreased blood transit time [3] Protected against the obesity-induced oxidative stress [54] Increased good cholesterol [56] Improved knee pain, stiffness, and physical function [57] Powerful in treating cisplatin-induced hearing loss [7] Table 1.…”
Section: Anti-cancer Activitymentioning
confidence: 99%
“…low-density cholesterol [56]. Daily supplementation of krill oil containing astaxanthin for six months improved knee pain, stiffness, and physical function in mild-tomoderate knee osteoarthritis patients [57]. Cisplatin-induced hearing loss has negative impact on the children's academic development and social integration.…”
Section: Summary Of Potential Therapeutic Health Benefits Of Astaxant...mentioning
confidence: 99%